Use of adaptive thermal storage system as smart load for voltage control and demand response - Luo,X; Lee,CK; Ng,WM; Yan,S; Chaudhuri,B; Hui,SYR (IEEE Transactions on Smart Grid, 2016)
This paper describes how a large-scale ice-thermal storage can be turned into a smart load for fast voltage control and demand-side management in power systems with intermittent renewable power, while maintaining its existing function of load shaving. The possibility of modifying a conventional thermal load has been practically demonstrated in a refrigerator using power electronics technology. With the help of an electric spring, the modified thermal load can reduce power imbalance in buildings while providing active and reactive power compensation for the power grid. Based on practical data, a building energy model incorporating a large-scale ice-thermal storage system has been successfully used to demonstrate the advantageous demand-response features using computer simulation of both grid connected and isolated power systems. The results indicate the potential of using ice-thermal storage in tall buildings in reducing voltage and frequency fluctuations in weak power grids.